2023
DOI: 10.5336/dentalsci.2022-92085
|View full text |Cite
|
Sign up to set email alerts
|

Readability and Contents Evaluation o Patient Informing Texts on Orthognathic Surgery in Turkish Websites: Methodological Study

Abstract: Orthognathic surgery is the applications performed to eliminate the disorders in the face and jaw structure of the person and to regain the normal functions of the teeth together with the jaws. Upon the increasing internet use, people reach the first knowledge about these surgeries, where serious complications can be seen, through websites. It is aimed to assess the Turkish texts released on the internet on orthognathic surgery regarding toreadability and contents in this study. Material and Methods: The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
0
0
1
Order By: Relevance
“…İnternet üzerinden ulaştıkları bu bilgi sesli ya da görüntülü video şeklinde olabilir ancak yapılan çalışmalar çoğunlukla metin şeklinde olduğunu göstermektedir. 12 Hasta bilgilendirme metinlerinin okunabilirliğinin değerlendirilmesi bu nedenle önemlidir.…”
Section: Discussionunclassified
“…İnternet üzerinden ulaştıkları bu bilgi sesli ya da görüntülü video şeklinde olabilir ancak yapılan çalışmalar çoğunlukla metin şeklinde olduğunu göstermektedir. 12 Hasta bilgilendirme metinlerinin okunabilirliğinin değerlendirilmesi bu nedenle önemlidir.…”
Section: Discussionunclassified
“…In a study evaluating the readability of intravenous and intramuscular injection informed consent forms, the readability was relatively low [18]. Another study conducted to evaluate the readability and content of patient information texts on orthognathic surgery on Turkish websites found that patient information texts have moderate reading difficulties, and complications are not sufficiently included [19].…”
Section: Discussionmentioning
confidence: 99%
“…Literatür taramasında benzer çalışmaların da etik kurul onayı almadıkları görülmüştür. [9][10][11][12]…”
Section: Gereç Ve Yöntemler Eti̇k Kurulunclassified
“…7 Bu amaçla literatürde çeşitli okunabilirlik analizleri sunulmuş olup, Türkçenin dil bilgisi ve kelime yapısına uygun olduğu belirtilen Ateşman'ın tanımladığı okunabilirlik analizi Türkçe metinlerde yaygın olarak kullanılmaktadır. [8][9][10][11][12] Yapılan araştırmalara göre internet kullanıcılarının %49'unun belirli bir sağlık sorunu veya tıbbi durum konusunda internete erişim sağladığı bildirilmiştir. 13 2003 yılında yapılan bir araştırmada ise bireylerin %85'inin doktor randevusu öncesinde karşılaştığı sağlık problemi ile ilgili internet araştırması yaptığı tespit edilmiştir.…”
unclassified